(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective (s): To determine the aetiological factors of preterm deliveries at Aminu Kano Teaching Hospital, Kano, Nigeria.. Materials and methods: This case-control study was conducted between 1st June 2006 and 31st May 2007.One hundred and forty eight women with preterm deliveries (cases) were compared with seven hundred and forty women who delivered at term (control). Data analysis was done using Epi- Info software (6.0 CDC Atlanta Georgia, USA). Univariate and multivariate logistic regression analysis were performed and the results were expressed as odds ratio (OR) with 95% confidence interval (CI). The contribution of the risk factors were estimated using chi square test and a p-value of < 0.05 was taken as significant. Results: The period incidence of preterm deliveries was 69 per 1000 births. Unbooked and low socioeconomic statuses, primigravidity, previous preterm deliveries, multiple pregnancies, pre-eclampsia, and malaria in pregnancy were significant risk factors that were associated with preterm delivery. These associations were still demonstrable after adjusting for confounding variables. Conclusion: Early girl marriage and childbearing and spontaneous pre-labour rupture of membranes not to be independent risk factors in this study. Women with risk factors should be managed in specialist hospitals. Bangladesh J Obstet Gynaecol, 2014; Vol. 29(1) : 9-14